Pengaruh Brand Ambassador Dan Brand Image Terhadap Keputusan Pembelian Pada Produk Scarlett : Studi Kasus Pada Mahasiswa Universitas Bhayangkara Jakarta Raya - Iq’maliyah; Dovina Navanti; Franciscus Dwikotjo Sri Sumantyo (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine partially and stimultan of the independent variable (free), namely brand ambassador (X1) and brand image (X2) and the dependent variable (bound), namely the purchase decision (Y). The method used in this research is a quantitative method with the sampling used, namely the sampling technique used in this study is non-probability, namely using purposive sampling. The population in this study were consumers who had bought Scarlett products at Bhayangkara University, Greater Jakarta. The number of samples used in this study were 100 respondents. Based on the research results, in the partial test (t) brand ambassadors have a negative and insignificant effect on purchasing decisions which has a t value of 0.381 > 1.984 t table with a significance value of 0.704 <0.05, brand image has a significant effect on purchasing decisions which has a t value of 5.242> 1.984 t table with a significance value of 0.000 <0.05. Furthermore, in the simultaneous test (F) the variables of product quality (X1) and price (X2) together have a significant effect on customer satisfaction (Y) which has a calculated F value of 14.585> 3.09 F table with a significance value of 0.000 <0.05. Then the decetermination test (R2) results that the correlation between the variables of product quality (X1) and price (X2) on customer satisfaction (Y) is 54.6%.